A fresh look at Sikh religion - Massey, James (Journal of religious culture, 2000)
Among the World religions Sikh religion comparatively is young. Numerically also the followers of Sikh religions are not large. According to the Census of India in the grand total of India's population i.e. 6659, 2879, 8491, the total number of Sikhs is 13,078. 146 out of which 8,937.210 are living in the Panjab province of India and the remaining 4,1409936 are scattered in the rest of the country.[1] These figures do not include the Sikhs living in other countries like the U.K., Canada, USA and other Western and Eastern countries. As these fig-ures show percentwise Sikhs are less than 2%, but they are having a special place among their country people an account of their special characteristics i.e. very hard workers, technicalminded, adventurous nature and willing to embrace all kinds of work. Because of their adventurous and enthusiastic nature, today they are found almost all over the world. On account, of visible insignia given by Sikhs' tenth Guru which includes uncut hair (and use of turban) makes the Sikhs' presence felt in any place. - In this brief study of Sikh religion I will be limiting myself only with one area. I will be looking from the historical perspectives how the Sikh religion came into existence and its growth during the period of 1469 AD - 1703 AD. This period is the most important, because - all the development of Sikh religion belongs to this era only. ...